(untitled) (Lafia Journal of Scientific and Industrial Research, 2025)
Culex quinquefasciatus, a vector of lymphatic filariasis and many other arboviral infections, remains a major public health concern, especially in regions lacking access to modern vector control tools. Growing resistance to synthetic insecticides has driven interest in eco-friendly alternatives, including plant-based larvicides such as Citrus sinensis (orange) peels. This study evaluated the larvicidal activity of ethanolic C. sinensis peel extract against Cx. quinquefasciatus larvae under laboratory conditions. Air-dried orange peels were pulverized and subjected to cold maceration in ethanol. Extracts were tested at concentration of 100–8,333 ppm on third to early fourth instar larvae, with four replicates per concentration. Mortality was recorded at 24 and 48 hours. LC₅₀ and LC₉₀ values were determined using linear interpolation. Data were analyzed using one-way ANOVA followed by Tukey’s post hoc test at a 5% significance level. High concentrations (1,667–8,333 ppm) caused complete mortality (25.00 ± 0.00) within five minutes, with no significant difference among treatments (p > 0.05). At moderate concentrations, mortality followed a dose-response trend: 400 ppm resulted in 54% and 57% mortality at 24 and 48 hours, while 800 and 1000 ppm achieved 100% mortality at both time points. Estimated LC₅₀ and LC₉₀ values were 385.2 and 713.0 ppm. No control group mortality was recorded throughout the study. C. sinensis peel extract exhibits potent larvicidal activity against Cx. Quinquefasciatus, particularly at concentrations above 400 ppm. Its efficacy low cost and availability suggest potential as a natural component in integrated mosquito control strategies, particularly in resource-limited settings.